Coenrad Laurens Coolen: Pioneer of Contextual Mission among Javanese Abangans - Nggebu, Sostenis (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
This historiographical article aims to describe Coolen as a pioneer of the indigenous church among the abangans in Ngoro, East Java in the 19th century, where he pioneered the ministry of indigenizing the gospel as an exciting new breakthrough. The discussion was conducted in stages of collecting historical data about Coolen, evaluating the obtained data, interpreting relevant data, and presenting the findings. The results show that Coolen was the initiator of the establishment of the ‘ngelmu’ Christian congregation among the abangans in Ngoro Village in the interior of East Java. He explained the secrets of ngelmu Kristen (lit., learning the Christianity) and appreciated Javanese culture as a new breakthrough in the ministry of preaching the gospel, compared to the Indische Kerk missionaries. However, some of his followers were more interested in joining Emde’s ministry pattern, so the outputs of his ministry were finally adopted into the Indische Kerk churches. Since then, the harvest of the abangans had stopped.